2015
DOI: 10.5194/acp-15-12645-2015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of global change upon United States air quality

Abstract: Abstract.To understand more fully the effects of global changes on ambient concentrations of ozone and particulate matter with aerodynamic diameter smaller than 2.5 µm (PM 2.5 ) in the United States (US), we conducted a comprehensive modeling effort to evaluate explicitly the effects of changes in climate, biogenic emissions, land use and global/regional anthropogenic emissions on ozone and PM 2.5 concentrations and composition. Results from the ECHAM5 global climate model driven with the A1B emission scenario… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 81 publications
2
17
0
Order By: Relevance
“…Because no reliable observations of nighttime cloud fraction exist, we focus on daytime measurements. On average, increased cloud fraction is associated with cooler surface air temperatures, but the relationship between cloud fraction and temperature can also have a strong seasonal cycle and vary by region (Groisman et al, 2000;Sun et al, 2000). Figure 8 shows the slopes of monthly mean cloud fraction (> 680 hPa) and surface temperature in summer from 2004 to 2012 over the southeast in daytime.…”
Section: Impact Of 2000-2050 Climate Changes On Pm 25 From Statisticmentioning
confidence: 99%
“…Because no reliable observations of nighttime cloud fraction exist, we focus on daytime measurements. On average, increased cloud fraction is associated with cooler surface air temperatures, but the relationship between cloud fraction and temperature can also have a strong seasonal cycle and vary by region (Groisman et al, 2000;Sun et al, 2000). Figure 8 shows the slopes of monthly mean cloud fraction (> 680 hPa) and surface temperature in summer from 2004 to 2012 over the southeast in daytime.…”
Section: Impact Of 2000-2050 Climate Changes On Pm 25 From Statisticmentioning
confidence: 99%
“…Numerous studies using regional CTMs that have considered both changing climate and changing emissions on future air pollutant concentrations have found that changes in emissions dominate (Nolte et al, 2008;Kelly et al, 2012;Colette et al, 2013;Trail et al, 2014;Day and Pandis, 2015;Gonzalez-Abraham et al, 2015;He et al, 2016). Modeled pollutant concentrations are highly sensitive to lateral chemical boundary conditions (e.g., Tang et al, 2007;Katragkou et al, 2010;Schere et al, 2012), and different assumptions regarding changes in long-range transport have been shown to have a significant impact on future pollutant levels (Nolte et al, 2008;Colette et al, 2013;Pfister et al, 2014;Gonzalez-Abraham et al, 2015;He et al, 2016;Zhang et al, 2016). Several previous studies have also highlighted the importance of rising levels of methane for ozone chemistry (Fiore et al, 2002;West and Fiore, 2005;Nolte et al, 2008).…”
Section: Chemical Transport Modelmentioning
confidence: 99%
“…Studies using global climate model (GCM) data to drive global or regional chemical transport models (CTMs) have found that climate change yields meteorological conditions that are more conducive to forming high O 3 , exacerbating summertime O 3 over polluted continental regions (Mickley et al, 2004;Leung and Gustafson Jr., 2005;Stevenson et al, 2006;Katragkou et al, 2011;Horton et al, 2012;Gao et al, 2013). Modeling studies conducted using mid-21st century climate data project up to 2-8 ppb increases in summer average ozone levels in the US, depending on climate change scenario and time period (e.g., Wu et al, 2008;Nolte et al, 2008;Weaver et al, 2009;Kelly et al, 2012;Trail et al, 2014;Pfister et al, 2014;Gonzalez-Abraham et al, 2015;Fann et al, 2015;He et al, 2016;Dionisio et al, 2017). This deterioration of air quality due to climate change is known as the "climate penalty" (Wu et al, 2008;Rasmussen et al, 2013) and could potentially offset some of the improvement in air quality that would otherwise occur due to reductions in ozone precursor emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Land use changes can affect air quality simulations through changes in emissions of biogenic volatile organic compounds, soil NO x , dust, smoke, and dry deposition of pollutants (Heald & Spracklen, 2015). For instance, future land use changes are predicted to increase PM 2.5 by 2050 in many parts of the United States due to increased biogenic emissions and SOA formation (Gonzalez‐Abraham et al, 2015). Uncertainties in dry deposition parameterization are estimated to introduce uncertainty of 5–15% in CMAQ PM 2.5 simulations (Saylor et al, 2019) or up to 40% in anthropogenic and 52% on biogenic organic aerosols over the CONUS in WRF‐Chem (Hodzic et al, 2014; Knote et al, 2015).…”
Section: Summary and Discussionmentioning
confidence: 99%